Brevvekslingen mellem Aage Friis og Friedrich Meinecke 1901-1949 - Rasmussen, Peter Hertel (Historisk Tidsskrift, 2023)
The Correspondence between Aage Friis and Friedrich Meinecke This essay describes and analyzes the friendship between two eminent historians: Professor Aage Friis (1870-1949), a Dane, and Friedrich Meinecke (1862-1954), the German professor and long-time editor of Historische Zeitschrift. From their correspondence, one learns that the two came to know each other around 1900 in the Prussian State Archives, where Friis pursued his interest in late 19th-century Danish-German relations and Meinecke worked as an archivist (he later became a professor in Strasbourg, then Freiburg im Breisgau and eventually Berlin). However, their correspondence only began in earnest after the First World War and culminated after the Second World War. Both were historicists and their preferred field of research was the 18th and 19th centuries, particularly the central role of foreign policy and, for Meinecke, the history of ideas. Politically they were not too far apart, Meinecke being moderately liberal and a convinced nationalist while Friis belonged to Denmark’s more leftist, albeit liberal, Det Radikale Venstre. Both were staunch opponents of the Nazis: Meinecke was forced into retirement by them in 1934 and Friis played a central role in Danish and Scandinavian efforts to help exiled German intellectuals. In their correspondence, Friis made great efforts to convey his deep conviction of the necessity of a friendship between Denmark and Germany. After the German defeat in 1945, Friis oversaw the Danish translation of Meinecke’s last work, The German Catastrophe, and their correspondence, coupled with Friis’ presentation of this monograph in Danish and Swedish newspapers, sheds light on the difficulties in promoting German culture at a time when respect for all things German was at a very low ebb.